Multimodal Imaging in AIDS-Related Ocular Cryptococcosis - Maria Fernanda Flores Herrera; Nicolas Dauby; Evelyne Maillart; Agnes Libois; Alberto Papaleo; Hind El Ouardighi; Laurence Postelmans; François Willermain; Dorine Makhoul (Case Reports in Ophthalmological Medicine)
Purpose. To report multimodal imaging findings in two cases of AIDS-related cryptococcal chorioretinitis associated with uveitis and vasculitis. Methods. Findings on clinical examination, color fundus photography, fluorescein and indocyanine green angiographies, and optical coherence tomography. Patients. Both patients were diagnosed with Cryptococcus neoformans meningitis in the setting of untreated HIV infection with CD4+ T cell count<100/mm3. Ocular manifestations occurred during the course of the antifungal therapy for meningitis. Results. In both cases, fundus showed vitritis. Fluorescein angiography allowed the characterization of vasculitis lesions, and indocyanine green angiography indicated choroidal involvement. In combination with optical coherence tomography, ICG and FA allowed the assessment of treatment response. Conclusion. These two cases reveal the potential of C. neoformans to infect almost all ocular structures and the critical role of multimodal imaging in baseline evaluation and in the follow-up of patients.